Johnson & Johnson’s Product Safety Issues and Ways the Company Can Address Those Issues - Monica Merli Anak James; Daisy Mui Hung Kee; Teoh Hui Xian; Kwong Ching Han; Khor Kae Ching; Maali Salem Alshammari (Asia Pacific Journal of Management and Education (APJME), 2019)
Johnson & Johnson was founded in 1886, which is a multinational medical device, pharmaceutical and consumer packaged goods manufacturing company. This company has 250 subsidiary companies which operate in 60 countries and their products are sold over 175 countries. The company was performing well since their establishment; however, J&J is facing numerous quality issues in later years. The first product safety issues arose in 1982, seven individuals died in Chicago, after ingesting cyanide- laced Tylenol capsules, and the company make a large recall of the capsules from retailers and it was known as the first major recalls in the American history. In 2010, a subsidiary of Johnson and Johnson has recalled children’s medicine after an inspection which claim that the products were not meet with the required manufacturing specification. Over the year 2016-2018, this company faced with numerous lawsuits related to its talcum powder products – Johnson’s Baby Powder and Shower-toShower body powder. The latest issue associated with this company was the powder contain harmful substances which might cause cancers. These issues had caused the public lost trust over the brand and the reputation was affected throughout the year. The purpose of this paper aims to analyse the product quality and safety issue and to discuss way to ensure pharmaceutical quality regarding Johnson & Johnson’s products. Besides quality control, company management also play a big role when facing this issue. Besides, we aim to find ways in which J&J could maintain its brand image and reputation as a trusted family company.